Philosophical Approaches to Literary Translation - Mohamed Sidi Mohamed Sidi Mahmoud (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
This article discusses the philosophical foundations of literary translation tackled by thinkers such as Walter Benjamin, Ezra Pound, Jacque Derrida and Georg Steiner. More specifically, it brings to view Benjamin’s call for the protection of the voice of the other, Pound’s archaism, Derrida’s notion of difference and Steiner’s hermeneutic motion. It pinpoints the limitations that characterize their views and the complications that frame their discussions. The article shows the extent to which their models help deconstruct the predominating domestication strategies which lead to the monolithic discourse of representation via translation. That is to say, they deconstruct the hegemony prevailed in traditional Western literary paradigms of translations. However, their models are philosophically oriented, without providing relevant methods for dealing with the linguistic gaps encountered in the literary translation.